A psychological approach to individual differences in intertemporal consumption patterns - Hermann Brandstätter; Werner Güth (Humboldt University of Berlin, Interdisciplinary Research Project 373: Quantification and Simulation of Economic Processes, 1998)
When people decide about saving and consumption across the various periods of their life time they take into account their life expectancy when comparing present and future needs and resources for satisfying them. The experimental design, applied at two sites (Humboldt-University at Berlin and Johannes-Kepler-University, Linz), aims at simulating a sequence of at least three, at most six saving vs. consumption decisions, depending on a stochastic manipulation of changes in life expectancy. In this report we focus on how personality characteristics influence the amount of consumption in single periods of life depending on life expectancy changes which may render previous consumption rates as too low or too high. According to Gray (1987) it was predicted and found that unstable introverts respond most, and stable extroverts least to this kind of 'punishment'. In addition, some exploratory findings involving the personality dimensions conscientiousness and tough-mindedness are reported.
urn:nbn:de:kobv:11-10057109
Keywords: 330; experimental economics; personality; intertemporal consumption and saving; individual differences